Find the condition for the line px + qy + r = 0 to touch the circle \[{x^2} + {y^2} = {a^2}\]. And also find the coordinates of the point of contact also.
Answer
Verified
510.6k+ views
Hint: Find the equation of tangent to the circle and equate it to the equation of the line to find the point of contact. Then substitute the point in the circle equation to find the condition.
Complete step-by-step answer:
Let us find the slope of the tangent to the circle which is \[\dfrac{{dy}}{{dx}}\].
Given equation of circle is as follows:
\[{x^2} + {y^2} = {a^2}...........(1)\]
Differentiating both sides with respect to x, we get:
\[2x + 2y\dfrac{{dy}}{{dx}} = 0\]
Taking 2x to the other side and simplifying, we get:
\[2y\dfrac{{dy}}{{dx}} = - 2x\]
Now, taking 2y to the other side and finding the slope as follows:
\[\dfrac{{dy}}{{dx}} = \dfrac{{ - x}}{y}\]
Let the tangent intersect the circle at the point (h, k), then we have the slope of the tangent as:
\[\dfrac{{dy}}{{dx}} = \dfrac{{ - h}}{k}.........(2)\]
The equation of the line having slope m and passing through a point (a, b) is given by:
\[y - b = m(x - a)\]
Using equation (2) for the equation of tangent in the above equation, we get:
\[y - k = \dfrac{{ - h}}{k}(x - h)\]
Simplifying this expression by multiplying k on both sides, we get:
\[ky - {k^2} = - hx + {h^2}\]
Gathering constant terms on the right-hand side, we have:
\[ky + hx = {h^2} + {k^2}..........(3)\]
The point (h, k) lies on the circle, therefore, using equation (1), we have:
\[{h^2} + {k^2} = {a^2}..........(4)\]
Substituting equation (4) in equation (3), we get:
\[ky + hx = {a^2}\]
\[ky + hx - {a^2} = 0..........(5)\]
The equation of the line is given by,
\[px + qy + r = 0..........(6)\]
From equation (5) and (6), we have:
\[\dfrac{p}{h} = \dfrac{q}{k} = - \dfrac{r}{{{a^2}}}\]
Hence, the value of h and k are as follows:
\[h = - \dfrac{{{a^2}}}{r}p...........(7)\]
\[k = - \dfrac{{{a^2}}}{r}q..........(8)\]
Hence, the point of intersection is \[\left( { - \dfrac{{{a^2}}}{r}p, - \dfrac{{{a^2}}}{r}q} \right)\].
Now, substitute equation (7) and (8) in equation (4).
\[{\left( { - \dfrac{{{a^2}}}{r}p} \right)^2} + {\left( { - \dfrac{{{a^2}}}{r}q} \right)^2} = {a^2}\]
\[\dfrac{{{a^4}}}{{{r^2}}}{p^2} + \dfrac{{{a^4}}}{{{r^2}}}{q^2} = {a^2}\]
\[\dfrac{{{a^4}}}{{{r^2}}}({p^2} + {q^2}) = {a^2}\]
\[{p^2} + {q^2} = \dfrac{{{r^2}}}{{{a^2}}}\]
Hence, the required condition is \[{p^2} + {q^2} = \dfrac{{{r^2}}}{{{a^2}}}\].
Note: You can directly solve the equation without finding the slope of the tangent if you know the formula for the equation of tangent to the circle at a point (h, k), that is, \[hx + ky - {a^2} = 0\].
Complete step-by-step answer:
Let us find the slope of the tangent to the circle which is \[\dfrac{{dy}}{{dx}}\].
Given equation of circle is as follows:
\[{x^2} + {y^2} = {a^2}...........(1)\]
Differentiating both sides with respect to x, we get:
\[2x + 2y\dfrac{{dy}}{{dx}} = 0\]
Taking 2x to the other side and simplifying, we get:
\[2y\dfrac{{dy}}{{dx}} = - 2x\]
Now, taking 2y to the other side and finding the slope as follows:
\[\dfrac{{dy}}{{dx}} = \dfrac{{ - x}}{y}\]
Let the tangent intersect the circle at the point (h, k), then we have the slope of the tangent as:
\[\dfrac{{dy}}{{dx}} = \dfrac{{ - h}}{k}.........(2)\]
The equation of the line having slope m and passing through a point (a, b) is given by:
\[y - b = m(x - a)\]
Using equation (2) for the equation of tangent in the above equation, we get:
\[y - k = \dfrac{{ - h}}{k}(x - h)\]
Simplifying this expression by multiplying k on both sides, we get:
\[ky - {k^2} = - hx + {h^2}\]
Gathering constant terms on the right-hand side, we have:
\[ky + hx = {h^2} + {k^2}..........(3)\]
The point (h, k) lies on the circle, therefore, using equation (1), we have:
\[{h^2} + {k^2} = {a^2}..........(4)\]
Substituting equation (4) in equation (3), we get:
\[ky + hx = {a^2}\]
\[ky + hx - {a^2} = 0..........(5)\]
The equation of the line is given by,
\[px + qy + r = 0..........(6)\]
From equation (5) and (6), we have:
\[\dfrac{p}{h} = \dfrac{q}{k} = - \dfrac{r}{{{a^2}}}\]
Hence, the value of h and k are as follows:
\[h = - \dfrac{{{a^2}}}{r}p...........(7)\]
\[k = - \dfrac{{{a^2}}}{r}q..........(8)\]
Hence, the point of intersection is \[\left( { - \dfrac{{{a^2}}}{r}p, - \dfrac{{{a^2}}}{r}q} \right)\].
Now, substitute equation (7) and (8) in equation (4).
\[{\left( { - \dfrac{{{a^2}}}{r}p} \right)^2} + {\left( { - \dfrac{{{a^2}}}{r}q} \right)^2} = {a^2}\]
\[\dfrac{{{a^4}}}{{{r^2}}}{p^2} + \dfrac{{{a^4}}}{{{r^2}}}{q^2} = {a^2}\]
\[\dfrac{{{a^4}}}{{{r^2}}}({p^2} + {q^2}) = {a^2}\]
\[{p^2} + {q^2} = \dfrac{{{r^2}}}{{{a^2}}}\]
Hence, the required condition is \[{p^2} + {q^2} = \dfrac{{{r^2}}}{{{a^2}}}\].
Note: You can directly solve the equation without finding the slope of the tangent if you know the formula for the equation of tangent to the circle at a point (h, k), that is, \[hx + ky - {a^2} = 0\].
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
Write an application to the principal requesting five class 10 english CBSE
Difference between mass and weight class 10 physics CBSE
What is Commercial Farming ? What are its types ? Explain them with Examples
What are five examples of facts and opinions class 10 english CBSE
Which state has the longest coastline in India A Tamil class 10 social science CBSE
10 examples of evaporation in daily life with explanations